Understanding the Meaning of an Advertisement Text through Interpersonal Function Analysis - Shaumiwaty; Endang Fatmawati; Syathroh, Isry Laila; Benesa Siagian, Claudya; Anggraini, Dwi Fitria; Herman, Herman (Anglophile Journal, 2024)
This research presents an interpersonal function analysis the writing in the advertisement. The researcher uses qualitative techniques and selects document studies because the researcher analyzes the data based on the context, namely writing and reading material. Beverage advertisements were chosen and analyzed through structural elements in interpersonal functions to determine the subject, finite, predicator, complement, and adjunct. In this study, researchers used advertisements for a drink taken from internet. The findings from this analysis are that there are several clauses that contain declarative negative moods and there are clauses that contain multiple declarative positive moods. The results of the data analysis ultimately show that the ad is declarative in nature, which is it provides information to the reader. The subject found 5(20,83%), finite found 7 (29,17%), predicator found 3 (12,5%), complement found 4 (16,67%), adjunct found 5 (20,83%). It can be concluded that the writing in the advertisement are giving information declarative with related in the function of interpersonal. Through this analysis the research team has shown how the interpersonal function analyzes the meaning of an advertisement, it is very important for us to know the meaning of a text to understand the content and purpose of the text so that readers do not experience misunderstandings in absorbing a text Keywords: Advertisement, Interpersonal Function, Meaning Text, Systemic Functional Linguistics